Altitude training - Is it beneficial? - Tillberg, N. (1997)
The purpose with altitude training is that it invokes several positive physiological effects, which are very similar to those caused by endurance training. Altitude training has been showed to improve performance at altitude, but the literature fails in providing consistent results about training effects at sea level after altitude training, no matter of training strategie (constant exposure, intermittent exposure or live high and train low). The majority of the studies in this area have several limitations that compromise the reliability of the results. However, anecdotal evidence from the literature shows that many coaches and athletes believe in and incorporate altitude training quite frequently in their seasonal training programs. Thus, the question whether altitude training enhances sea level performance remains controversial. At the present time, there is no scientific evidence in the literature showing that altitude training improves sea level performances in any athlete.